Acolpenteron australe sp. n. (Dactylogyridae:Dactylogyrinae), a new species from the ureters of Percichthys trucha (Perciformes:Percichthyidae) in Patagonia (Argentina) - Viozzi, Gustavo P; Brugni, Norma L (Folia parasitologica, 2003)
Acolpenceron australe sp. n. (Dactylogyridae, Dactylogyrinae) is described from ureters and renal tubules of Percichthys trucha (Cuvier et Valenciennes) (Perciformes, Percichthyidae) from Andean Patagonian lakes. The new species has a haptor with 14 hooks, with shanks comprised of two subunits. It has overlapped intercaecal gonads, male copulatory organ as a sclerotized tube with one counterclockwise coil and a J-shaped accessory piece. It differs from the other species of Acolpenteron by having a non-forked accessory piece. This is the first monogenean species described from a percichthyid host in South America.
Keywords: Animals; mužské pohlaví; Fish Diseases; Perciformes; zvířata; Trematode Infections; nemoci ryb; Argentina; Male; Ureter; ureter; infekce červy třídy Trematoda; Trematoda